Effect of Implementation of Industry 4.0 on Customer Satisfaction and Loyalty in Malaysia - Eshkiki , Mir Mostafa Seyed Mortezavi; Ismail, Hishamuddin Bin; Yen, Yuen Yee (Journal of Ecohumanism, 2025)
Nowadays in Malaysia, increased use of smart technologies by customers is leading to recognition of their influence on practitioners’ companies. However, academic literature fails to acknowledge the influence of smart technology usage on customer satisfaction and loyalty. This is because most research focuses on companies' perspectives and how they will adapt to the new technology. Even in this regard, we can refer to the policy of countries such as Malaysia, where most of the policy is focused on how it is presented and used technology by companies but in this research, the acceptance and use of technology is examined from the perspective of customers. This research utilizes explanatory research at the preliminary stage to examine this phenomenon in SMEs setting. Based on the academic information found in the body of existing literature, a conceptual framework was developed and tested by a convenience sample survey of 383 SMEs customers in Malaysia. Furthermore, the differences in technological readiness by age, gender, and educational attainment have been investigated in this study.